Students’ Ability in Solving HOTS-Based Chemistry Problems: A Case of High School Students at Palembang City - Nawawi, Effendi; Suharman, Andi; Mulyono, Budi; Ad'hiya, Eka (FKIP Universitas Lampung, 2023)
Abstract: This research aims to analysis students ability in solving HOTS based chemistry problems. This research is qualitative research with a case study approach. Data collection was carried out through observation, tests and interviews. The research results show that high-level thinking skills which include the level of analytical skills have an average student achievement of 16.162%, the level of evaluation thinking skills reaches 8.937%, and the level of creative thinking skills reaches a maximum of 14.888%. score 100. Based on the interview results, it is known that students' high-level thinking abilities are relatively low because they are not used to working on HOTS questions. Therefore, it can be concluded that high-level thinking abilities need to continue to be improved, and one way to achieve this is through solving HOTS based chemistry problems. Keywords: higher order thinking, chemistry problems, case study. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat kemampuan berpikir tingkat tinggi dalam menyelesaikan permasalahan Kimia HOTS (High-Order Thinking Skills). Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan melalui observasi, tes, dan wawancara. Hasil penelitian menunjukkan bahwa keterampilan berpikir tingkat tinggi yang meliputi tingkat keterampilan analisis mempunyai rata-rata pencapaian siswa sebesar 16,162%, tingkat keterampilan berpikir evaluasi mencapai 8,937%, dan tingkat keterampilan berpikir kreatif mencapai maksimal 14,888%. skor 100. Berdasarkan hasil wawancara diketahui bahwa kemampuan berpikir tingkat tinggi siswa tergolong rendah karena belum terbiasa mengerjakan soal HOTS. Oleh karena itu, dapat disimpulkan bahwa kemampuan berpikir tingkat tinggi perlu terus ditingkatkan, dan salah satu cara untuk mencapainya adalah melalui penyelesaian soal HOTS Kimia. Kata kunci: kemampuan berpikir tingkat tinggi, soal kimia, studi kasus.DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp545-555